2022
DOI: 10.3390/antibiotics11060708
|View full text |Cite
|
Sign up to set email alerts
|

Nanostructured Antibiotics and Their Emerging Medicinal Applications: An Overview of Nanoantibiotics

Abstract: Bacterial strains resistant to antimicrobial treatments, such as antibiotics, have emerged as serious clinical problems, necessitating the development of novel bactericidal materials. Nanostructures with particle sizes ranging from 1 to 100 nanometers have appeared recently as novel antibacterial agents, which are also known as “nanoantibiotics”. Nanomaterials have been shown to exert greater antibacterial effects on Gram-positive and Gram-negative bacteria across several studies. Antibacterial nanofilms for m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 97 publications
(111 reference statements)
0
20
0
Order By: Relevance
“…Other research has indicated that the predominant cause of the antibacterial mechanism could be due to the disturbance of cell membrane activity 59 , 60 . However, Modi et al 61 stated that gram-negative antibiotic-resistant bacteria, for example, Klebsiella pneumoniae and Escherichia coli , have low sensitivity to colloidal ZnO NPs compared to gram-positive antibiotic-resistant bacteria. As previously discussed, the production of intercellular reactive oxygen species, such as hydrogen peroxide, an oxidizing element that harms bacterial cells, may also cause this mechanism 62 .…”
Section: Discussionmentioning
confidence: 99%
“…Other research has indicated that the predominant cause of the antibacterial mechanism could be due to the disturbance of cell membrane activity 59 , 60 . However, Modi et al 61 stated that gram-negative antibiotic-resistant bacteria, for example, Klebsiella pneumoniae and Escherichia coli , have low sensitivity to colloidal ZnO NPs compared to gram-positive antibiotic-resistant bacteria. As previously discussed, the production of intercellular reactive oxygen species, such as hydrogen peroxide, an oxidizing element that harms bacterial cells, may also cause this mechanism 62 .…”
Section: Discussionmentioning
confidence: 99%
“…There are lesser-known factors that influence and alter nasal microbiota; age, season, and climate may also alter the nasal microbiota [ 31 ]. Additionally, air pollution, even low exposure, may influence the nasal microbiota during the first year of life; especially, exposure to air pollutants PM 2.5 and NO 2 is associated with nasal microbiota alteration, respiratory infections, and asthma development during early life [ 32 , 33 ].…”
Section: Air Pollution Impact On Nasal Microbiotamentioning
confidence: 99%
“…These optical and electronic characteristics provide an outstanding catalytic action against targeted applications. [4,5]. The associated electronic configurations of both the Ag and Au NPs found much better as bimetallic nanocatalysts due to their intra-bands structure and combined surface plasmon resonance (SPR, produced by the combined fluctuation of the valance band electrons after irradiated by electromagnetic wave) and that is why both candidates are mainly focused for biomedical uses as compared to other noble metals.…”
Section: Introductionmentioning
confidence: 99%
“…When the particular incident light interacts with Ag and Au particles, the conduction bands electron promotes to the valance bands and combined fluctuates with the similar frequencies of incident wavelength of light. This phenomenon is called SPR which is studied in noble metal surfaces [5][6][7]. Variety morphologies offer fascinating chances for biomolecules or microbes to disperse and come into interaction with one another at the surface, enabling individuals to properly manage their specific functions.…”
Section: Introductionmentioning
confidence: 99%